Assessment of Platelet Thrombus Formation under Flow Conditions in Adult Patients with COVID-19: An Observational Study - Ghirardello, Stefano; Lecchi, Anna; Artoni, Andrea; Panigada, Mauro; Aliberti, Stefano; Scalambrino, Erica; La Marca, Silvia; Boscarino, Marco; Gramegna, Andrea; Properzi, Paolo; Abruzzese, Chiara; Blasi, Francesco; Grasselli, Giacomo; Mosca, Fabio; Tripodi, Armando; Peyvandi, Flora (Thrombosis and Haemostasis, 2021)
Background Coronavirus disease 2019 (COVID-19) is associated with systemic inflammation, which may dysregulate platelet function. Total Thrombus-Formation Analysis System (T-TAS) is a flow-chamber device that analyses platelet-mediated thrombus formation in capillary channels through the following parameters: (1) the area under the flow-pressure curve (AUC), (2) occlusion start time (OST), time needed to reach OST, and (3) occlusion time (OT), time needed to reach the occlusion pressure.Methods and Findings Sixty-one COVID-19 patients admitted to intensive, subintensive, and low intensive care were prospectively enrolled according to the time of admission: group A (up to 8 days) (n = 18); group B (from 9 to 21 days) (n = 19), and group C ( > 21 days) (n = 24). T-TAS measurements were performed at enrolment and after 7 days. Median OST was similar among groups. AUC was lower in group A compared to B (p = 0.001) and C (p = 0.033). OT was longer in group A compared to B (p = 0.001) and C (p = 0.028). Platelet count (PC) was higher in group B compared to A (p = 0.024). The linear regression showed that OT and AUC were independent from PC in group A (OT: 0.149 [95% confidence interval [CI]: –0.326 to 0.624], p = 0.513 and AUC: 0.005 [95% CI: –0.008 to 0.017], p = 0,447). In contrast, in group B, PC was associated with OT (–0.019 [–0.028 to 0.008], p = 0.023) and AUC (0.749 [0.358–1.139], p = 0,015), similarly to group C. Conversely, patients with different illness severity had similar T-TAS parameters.Conclusion COVID-19 patients display an impaired platelet thrombus formation in the early phase of the disease compared to later stages and controls, independently from illness severity.
Keywords: platelets; platelet function; antiplatelet therapy; arterial thrombosis; blood coagulation; T-TAS; venous thromboembolism